Makna Digitalisasi Ekonomi terhadap Transformasi Gaya Hidup Generasi Z: Studi Kualitatif Mahasiswa UNWIRA - Agustina F. Wolor; Theresia B. Rangga; Alicia J. V. Nggadas; Yohanes P. Lian (AKUNTANSI 45, 2026)
This research aims to examine the meaning of economic digitalization in the lives of Generation Z students at the Catholic University of Widya Mandira (UNWIRA), particularly in the context of lifestyle transformation. Employing a descriptive qualitative research method, the study results indicate that the majority of Gen Z students actively use digital economic services for various activities, ranging from online shopping and investment to e-wallets, and have established an integrated digital lifestyle pattern. Theoretically, this meaning is explained through three main frameworks: 1) Lifestyle Transformation Theory, which accounts for changes in lifestyle, social patterns, and the structure of individual activities due to technological development; 2) Uses and Gratifications Theory, which views students as actively utilizing digital technology to meet informational, entertainment, and social needs while simultaneously forming their identity; and 3) Symbolic Interactionism, which emphasizes that economic digitalization is interpreted through social interaction and functions as a symbol of modernity, prestige, and self-empowerment. For UNWIRA students, economic digitalization is not merely a technological phenomenon but also a representation of the process of forming a modern identity and lifestyle. The implications of these findings underscore the importance of enhancing digital and financial literacy to minimize the risk of consumerism and digital dependence.